EFFECT OF MANURES AND FERTILIZERS ON POTATO (SOLANUM TUBEROSUM) PRODUCTION - Kushwah, V S.; Singh, S P; Lal, S S (Potato Journal, 2013)
Experiment was conducted during rabi season (2004-05) on silty clay loam soil at Gwalior to study the effect of FYM, Nadep compost, Vermi compost and inorganic NPK fertilizers on yield and economics of potato. Application of FYM, Nadep compost and vermi compost alone or in combination did not influence tuber yield significantly. However, organic manures @ 7.5 t/ha in combination with 50% recommended dose of NPK significantly increased tuber yield. The highest tuber yield (321 q/ha) was recorded with 100% recommended dose of NPK fertilizers, and was significantly higher than all other treatments. The highest incremental benefit cost ratio, IBCR (7.5) was obtained with 50% recommended dose of NPK.